Construction and Analysis of a ceRNA Network in Cardiac Fibroblast During Fibrosis Based on in vivo and in vitro Data - Gao, Qing-Yuan; Zhang, Hai-Feng; Chen, Zhi-Teng; Li, Yue-Wei; Wang, Shao-Hua; Wen, Zhu-Zhi; Xie, Yong; Mai, Jing-Ting; Wang, Jing-Feng; Chen, Yang-Xin (Frontiers in Genetics, 2021)
Aims: Activation of cardiac fibroblasts (CF) is crucial to cardiac fibrosis. We constructed a cardiac fibroblast-related competing endogenous RNA (ceRNA) network. Potential functions related to fibrosis of “hub genes” in this ceRNA network were explored. Methods and Materials: The Gene Expression Omnibus database was searched for eligible datasets. Differentially expressed messenger (m)RNA (DE-mRNA) and long non-coding (lnc)RNA (DE-lncRNA) were identified. microRNA were predicted and validated. A predicted ceRNA network was constructed and visualized by Cytoscape, and ceRNA crosstalk was validated. Single Gene Set Enrichment Analysis (SGSEA) was done and the Comparative Toxicogenomics Database (CTD) was employed to analyze the most closely associated pathways and diseases of DE-mRNA in the ceRNA network. The functions of DE-mRNA and DE-lncRNA in the ceRNA network were validated by small interfering (si)RNA depletion. Results: The GSE97358 and GSE116250 datasets (which described differentially expressed genes in human cardiac fibroblasts and failing ventricles, respectively) were used for analyses. Four-hundred and twenty DE-mRNA and 39 DE-lncRNA, and 369 DE-mRNA and 93 DE-lncRNA were identified, respectively, in GSE97358 and GSE116250 datasets. Most of the genes were related to signal transduction, cytokine activity, and cell proliferation. Thirteen DE-mRNA with the same expression tendency were overlapped in the two datasets. Twenty-three candidate microRNA were predicted and expression of 11 were different. Only two DE-lncRNA were paired to any one of 11 microRNA. Finally, two mRNA (ADAM metallopeptidase domain 19, (ADAM19) and transforming growth factor beta induced, (TGFBI)), three microRNA (miR-9-5p, miR-124-3p and miR-153-3p) and two lncRNA (LINC00511 and SNHG15) constituted our ceRNA network. siRNA against LINC00511 increased miR-124-3p and miR-9-5p expression, and decreased ADAM19 and TGFBI expression, whereas siRNA against SNHG15 increased miR-153-3p and decreased ADAM19 expression. ADAM19 and TGFBI were closely related to the TGF-β1 pathway and cardiac fibrosis, as shown by SGSEA and CTD, respectively. Depletion of two mRNA or two lncRNA could alleviate CF activation. Conclusions: The CF-specific ceRNA network, including 2 lncRNA, 3 miRNA, and 2 mRNA, played a crucial role during cardiac fibrosis, which provided potential target genes in this field.